(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2020)
The article examines the folklore metatext functions in the novel "Vichnyk. Confession on the passage of the spirit" by M. Dochynets. Drawing on modern concepts of metatext, understanding of folklore as a complex of folk knowledge, which embodied in artistic text by various forms, the author determines the connection of the content of the explored novel with folklore consciousness and outlines the folklore metatext functions. The use of a large formal and content arsenal of Ukrainian folklore by writer contributes to the formation of a holistic ideological and artistic concept of the work, defines its semantic load, simulates the narrative strategy of the text. The novel involves a wide genre of folklore system (prayers-orders, legends, parables, proverbs and sayings, medical orders); the concepts of the worldviews, the traditional folklore techniques of the images creation, which allows the holder of cultural national tradition to perceive the work at the archetypal-associative level. Folklore primary basis of the work performs a text-forming function, outlines its communicative setting and contributes to the reliability of the described. This approach leads to the reader’s co-creation and determines the collectivity of the author’s narrative.